Investigating Social Factors Affecting Social Tolerance (Case study: Ethnic Groups Living in Ahvaz) - Amirhosein zandi darehgharibi; Shapour Behyan; reza esmaeili (توسعه اجتماعی, 2021)
In the past, the diversity of cultures, languages, ethnicities and other elements of social life was less, and as a result, tolerating each other's differences and beliefs was not an important issue; But with the increasing growth and development of communication in all fields, on the one hand, cultural, ethnic, linguistic and religious diversity has increased, and on the other hand, the amount of interactions between people has doubled so that without a minimum of social tolerance and tolerance of different opinions. Otherwise, it will be impossible to live normally. Accordingly, the present study aimed to investigate the social and cultural factors affecting the social tolerance of ethnic groups in Ahvaz, selected 384 citizens through multi-stage sampling and collected data using a questionnaire in SPSS23 software has analyzed. Findings showed that there is no significant relationship between ethnicity and ethnic diversity variables with social tolerance. But there is a significant and direct relationship between the variables of citizenship rights (0.138) and political participation (0.360) with the variable of social tolerance and between the variable of group convergence (-0.205) and the variable of social tolerance.